Role of Maintenance Therapy with Decitabine in Acute Myeloid Leukemia in First Remission: A Prospective Interventional Study from a Tertiary Care Center in Eastern India - Bhattacharya, Subham; Banerjee, Apurba; Dolai, Tuphan Kanti; Sadhukhan, Sanjoy Kumar (Indian Journal of Medical and Paediatric Oncology, 2025)
Major advances in the diagnostic methodologies and technological progress have led to successful development of many targeted agents in the management of acute myeloid leukemia (AML). At present, standard of care of AML postremission depends on the molecular risk stratification of the disease. Despite incorporation of newer agents with chemotherapy, relapse remains a major problem. To address this unmet need, many investigators have used hypomethylating and other targeted drugs as maintenance after remission induction in AML in different clinical studies with variable results.We conducted this study to determine the efficacy of maintenance decitabine in AML after remission and to assess its side effects.This is a prospective interventional study. After considering the inclusion and exclusion criteria, patients with a diagnosis of AML were given 3 + 7 induction. All adverse risk patients were counseled for allogeneic hematopoietic stem cell transplantation and removed from the study if they opted for that. After documenting remission, patients were given three high-dose cytarabine (HIDAC) as consolidation. Those who remain on remission after third HIDAC were started on decitabine maintenance at 12 weeks' interval. A total of 20 patients were included. They were followed up at 3 monthly intervals by complete blood count, peripheral blood smear, and bone marrow aspiration during maintenance. Disease-free survival (DFS) and overall survival (OS) were calculated and compared with historical control. Toxicity and side effects of decitabine were also assessed.At a median follow-up of 29 months, the median DFS and OS were 20.5 and 27.5 months, respectively. Seven patients experienced grade 3 and 1 patient grade 4 hematological adverse events. One patient died due to febrile neutropenia.Decitabine may be considered as safe and effective maintenance agent in AML after achieving first remission.
Keywords: non-M3 AML; decitabine; maintenance; disease-free and overall survival